Amendment 14 civil rights of citizens - Fabian, Rhonda; Baber, Jerry; Cambridge Educational (Monmouth Junction, N.J. : Cambridge Educational, 2004)
This program explores the fourteenth amendment: its orgins, real-world applications, history of interpretation in the nation's courts, and implications for the future. Combining computer graphics, original live-action video, historical artwork, and archival footage with narration and interviews, this program illustrates the importance of the amendments in the history of the United States
Title from cover
Adapted from Amendments to the Constitution: a brief legislative history
Executive producer, Edward T. Gardner ; camera, Mark Dombrow ; editord, Jonathan M. Donley, Ron Schindlinger ; writer, Aaron Myers, Jack Phelan, Rhonda Fabian
Narrator : Gene Shay
DVD format
Keywords: United States; Constitutional amendments -- United States; Civil rights -- United States